Muslim youth environmentalists in Indonesia. (9th August 2021) - Nilan, Pam
ABSTRACT: This paper examines interview data from 20 young Muslim environmentalists in Indonesia. The data comes from a much broader research project on how people in Indonesia become environmentalists. The data for this extensive, multi-method Australian Research Council project undertaken between 2013 and 2017 was collected according to the overall aim of finding out how Indonesian people, in this instance, Indonesian youth, become environmentalists. There were specific research questions attached to the survey component of the larger project. However, there were no specific research questions as such guiding the ethnographic component of the data collection, to which the interviews here belong. Interviewees were simply asked to talk about their involvement in the environmental movement. The specific finding reported here is that these young activists based their environmentalism firmly on their Muslim faith. Their 'ecological habitus' seemed to be amplified by their 'sacred capital' as a form of symbolic capital. They actively engaged religious doxa that encourages them to see themselves as khalifah – God's lieutenants on earth; the need to take upon oneself the sacred task of stewardship of the natural world. This finding for Indonesia illustrates the growing popularity of 'green Islam' as a global youth imperative.